Understanding resource consumption and sustainability in the built environment - Stillwell, Ashlynn S; Cominola, Andrea; Beal, C D (Environmental research, infrastructure and sustainability : ERIS, 2023)
The built environment and the communities that contribute to its infrastructure, services, and systems are important aspects of human life. As urbanization increases, time spent indoors also increases, with urban residents spending most of their time indoors. This indoor lifestyle concentrates the effects of water, energy, and food consumption in the built environment, with local, regional, and global implications for interconnected resources and their supply chains. As such, resource consumption in the built environment has sustainability implications, especially with increasing populations and living standards. This focus issue, ‘Resource Consumption and Sustainability in the Built Environment’, examines infrastructure and sustainability from many perspectives. The articles investigate water, energy, and/or food consumption across various scales, ranging from a single household to nationwide supply chains to global climate models. Each paper in this issue considers essential elements of context, since water, energy, and food have local and global sustainability considerations, along with multi-sector dependencies within urban metabolism. Digital technologies, data, and modeling approaches are opening new opportunities for better monitoring and understanding of the built environment. In an uncertain future, understanding resource consumption in the built environment and its implications for the environment and society is a critical aspect of overall human health and well-being. In-depth knowledge of the dynamics shaping the built environment is paramount to supporting adaptive infrastructure planning and management, including supply and demand interventions to help cities and communities become climate neutral while increasing equity in access and affordability of resources and services.